Odpowiedź :
Odpowiedź:
d) 7x+3=17
7x=14
x=2
e) 5x +21 -9x=5
-4x=-16
x=4
f)6x-23-x=7
5x=30
x=6
g)4x-19+2x=23
6x=42
x=7
h)7x+6-5x=24
2x=18
x=9
d)7x=3x-4
4x=4
x=1
e)4x=28-3x
7x=28
x=4
f)9x=5x-8
4x=8
x=2
g)2x=12-4x
6x=12
x=2
h)3x=x+10
2x=10
x=5
i)5x=3x-12
2x=-12
x=-6
a)6x+4=9
6x=5
x= 1.2
b)3a-1.3=11
3a=12.3
a=4.1
c)3/4+5x=4,75
5x=5,5
x=1,1
d)2y-0,3=5,3
2y=5,6
y=2,8
e)9+0,5x=10
0,5x=1
x=2
f)1/6t-7=1
1/6x=8
x=48
Szczegółowe wyjaśnienie:
d) 2x+3+5x=17
7x=17-3
7x=14 /:7
x=2
e)5x+21-9x=5
-4x=5-21
-4x=-16 /:(-4)
x=4
f)6x-23-x=7
5x=7+23
5x=30 /:5
x=6
g)4x-19+2x=23
6x=23+19
6x=42 /:6
x=7
h) 7x+6-5x=24
2x=24-6
2x=18 /:2
x=9
i)9x+12-3x=18
6x=18-12
6x=6 /:6
x=1
NASTEPNE:
d)7x=3x-4
7x-3x=-4
4x=-4 /:4
x=-4
e) 4x=28-3x
4x+3x=28
7x=28 /:7
x=4
f)9x=5x-8
9x-5x=-8
4x=-8 /:4
x=-2
g)2x=12-4x
2x+4x=12
6x=12 /:6
x=2
h)3x=x+10
3x-x=10
2x=10 /:2
x=5
i)5x=3x-12
5x-3x=-12
2x=-12 /:2
x=-6
NASTĘPNE:
a)6x+4=9
6x=9-4
6x=5 /:6
x=5/6 (ułamek)
b)3a-1,3=11
3a=11+1,3
3a=12,3 /:3
a=4,1
c)3/4+5x=4,75
5x=4,75+0,75
5x=5,5 /:5
x=1,1
d)2y-0,3=5,3
2y=5,3+0,3
2y=5,6 /:2
y=2,8
e)9+0,5x=10
0,5x=10-9
0,5x=1 /:0,5
x=2
f)1/6t-7=1
1/6t=1+7
1/6t=8 /: 1/6
t= 48
jak czegos nie rozumiesz to pisz
7x=17-3
7x=14 /:7
x=2
e)5x+21-9x=5
-4x=5-21
-4x=-16 /:(-4)
x=4
f)6x-23-x=7
5x=7+23
5x=30 /:5
x=6
g)4x-19+2x=23
6x=23+19
6x=42 /:6
x=7
h) 7x+6-5x=24
2x=24-6
2x=18 /:2
x=9
i)9x+12-3x=18
6x=18-12
6x=6 /:6
x=1
NASTEPNE:
d)7x=3x-4
7x-3x=-4
4x=-4 /:4
x=-4
e) 4x=28-3x
4x+3x=28
7x=28 /:7
x=4
f)9x=5x-8
9x-5x=-8
4x=-8 /:4
x=-2
g)2x=12-4x
2x+4x=12
6x=12 /:6
x=2
h)3x=x+10
3x-x=10
2x=10 /:2
x=5
i)5x=3x-12
5x-3x=-12
2x=-12 /:2
x=-6
NASTĘPNE:
a)6x+4=9
6x=9-4
6x=5 /:6
x=5/6 (ułamek)
b)3a-1,3=11
3a=11+1,3
3a=12,3 /:3
a=4,1
c)3/4+5x=4,75
5x=4,75+0,75
5x=5,5 /:5
x=1,1
d)2y-0,3=5,3
2y=5,3+0,3
2y=5,6 /:2
y=2,8
e)9+0,5x=10
0,5x=10-9
0,5x=1 /:0,5
x=2
f)1/6t-7=1
1/6t=1+7
1/6t=8 /: 1/6
t= 48
jak czegos nie rozumiesz to pisz